Atmospheric fate of ketolimonene part 2: Highly oxygenated molecules (HOMs) and secondary organic aerosol (SOA) formation from NO3-initiated oxidation - Sandy Solaiman; Prasanna Kumar Bej; Cécile Coeur; Nicolas Houzel; Hayley Furnell; Emma Galloway; Fabrice Cazier; Amir Ben Brik; Mixtli Campos-Pineda; Estelle Roth; Albert A. Ruth; John C. Wenger; et al. (Journal of Environmental Sciences, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

VOC emissions from asphalt: Laboratory oxidation, ultrafine particle formation, and urban air quality implications - Prasanna Kumar Bej; Saba Shariati; Anais Lostier; Sandy Solaiman; Hui Chen; Alexandre Tomas; Nicolas Houzel; Pierre-Edouard Danjou; Cécile Coeur; Manolis N. Romanias; Elham Fini (Journal of Hazardous Materials, 2026)

Atmospheric fate of ketolimonene part 1: temperature-dependent kinetics and gas-phase products from NO3-initiated oxidation - Sandy Solaiman; Prasanna Kumar Bej; Cécile Coeur; Nicolas Houzel; Hayley Furnell; Emma Galloway; Amir Ben Brik; Mixtli Campos-Pineda; Estelle Roth; Albert A. Ruth; John C. Wenger; Alexandre Tomas; et al. (Journal of Environmental Sciences, 2026)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Review of Sarcophagidae and Tachinidae (Diptera) Parasitic Flies Associated to Mocis latipes (Guenée, 1852) (Lepidoptera: Erebidae), with Novel Parasitism Records for Alagoas and Brazil - Elio Cesar Guzzo; Alexandre Specht; José Cícero Ferreira dos Santos; Paulo de Albuquerque Silva; Ronaldo Toma (Neotropical Entomology, 2025)

Changing isotope compositions of Mg, Ca and Sr in bulk crystalline rocks toward the weathering front: Disentangling inputs of geogenic base cations into ecosystems - Martin Novak; Yulia V. Erban Kochergina; Chris Holmden; Alexandre V. Andronikov; Vaclav Kachlik; Jana Kotkova; Irina E. Andronikova; James W. Kirchner; Jakub Hruška; Frantisek Veselovsky; Frantisek Laufek; Ondrej Pour; et al. (Applied Geochemistry, 2025)

Tissue distribution of Ocimum basilicum essential oil in Nile tilapia Oreochromis niloticus after anesthesia - Emilly Monteiro Lopes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Alexandre Vaz da Silva; Caio Francisco Santana Farias; Domickson Silva Costa; Ana Paula de Souza; Danilo Vitor Vilhena Batista; Silvia Terra Fontes; Gabriela Tomas Jerônimo; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Veterinary Research Communications, 2025)

Nighttime chemistry of furanoids and terpenes: Temperature dependent kinetics with NO3 radicals and insights into the reaction mechanism - Fatima Al Ali; Vincent Gaudion; Alexandre Tomas; Nicolas Houzel; Cécile Cœur; Manolis N. Romanias (Atmospheric Environment, 2025)

Temperature-induced changes in the hematological and biochemical parameters of Nile tilapia anesthetized with Ocimum basilicum - Paola Capistrano dos Santos; Emilly Monteiro Lopes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Alexandre Vaz da Silva; Domickson Silva Costa; Marília Tedesco; Gabriela Tomas Jerônimo; Maurício Laterça Martins (Aquaculture International, 2025)

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Antimicrobial and anthelmintic effects of copper nanoparticles against Koi carp parasites and their toxicity - Gracienhe Gomes dos Santos; Liseth Vanessa Perengue Riofrio; Ana Paula Sousa; Paola Capistrano Santos; Alexandre Vaz Silva; Emilly Monteiro Lopes; Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Giulia Beatrice Ferreira; Graziella Vivine Gonçalves de Matos Silva; Marilia Tedesco; Diego José Nogueira; et al. (Journal of Fish Diseases, 2024)
This study investigated the in vitro antimicrobial and anthelmintic effect of copper nanoparticles (CuNPs) against the bacterium Aeromonas hydrophila , the monogeneans Dactylogyrus minutus , Dactylogyrus extensus , Gyrodactylus cyprini , and the cestode Schyzocotyle acheilognathi , as well as their toxicity to Cyprinus carpio Koi. In the antimicrobial in vitro test, the inhibition zone method and minimum inhibitory concentration (MIC) were performed. In order to determine the time and efficacy of monogenean parasite mortality, the parasites were exposed to CuNP concentrations of 20, 50, 100, 150, 200, and 300 mg L −1 , and a control group with tank water and one with copper sulphate pentahydrate (CuSO 4 . 5 H 2 O) at a concentration of 0.3 mg L −1 , performed in triplicate. The parasites were observed every 10 min for 300 min, and mortality was recorded. For the cestodes, parasites were immersed in CuNP concentrations of 50, 100, 150, and 300 mg L −1 . At the end of the in vitro tests, the anthelmintic efficacy of each treatment was calculated. To assess the tolerance and toxicity in fish, they were exposed to CuNP concentrations of 0.6, 1.25, 2.5, 5, 10, 20, and 50 mg L −1 for 12 h. The MIC demonstrated that CuNPs effectively inhibited the growth of A . hydrophila up to a dilution of 12,500 mg L −1 and showed an inhibition zone of 14.0 ± 1.6 mm for CuNPs. The results of anthelmintic activity showed a dose‐dependent effect of concentration for both groups of parasites, with the most effective concentration being 300 mg L −1 in 120 min. In the toxicity test, the carps showed tolerance to lower concentrations. The study indicated that CuNPs were effective against the studied pathogens. However, it proved to be toxic to fish at high concentrations. The use of low concentrations is recommended still requires further investigation.

Economic Appropriation of Ecosystem Services in Rural Landscapes: Fundamentals and Challenges for an Institutional Change Approach - Alexandre Toshiro Igari; Luiza Friedrichsen Canellas; Sergio Villamayor-Tomas; Leandro Reverberi Tambosi (Current Landscape Ecology Reports, 2024)

Sizeable net export of base cations from a Carpathian flysch catchment indicates their geogenic origin while the 26Mg/24Mg, 44Ca/40Ca and 87Sr/86Sr isotope ratios in runoff are indistinguishable from atmospheric input - Martin Novak; Yulia V. Erban Kochergina; Alexandre V. Andronikov; Chris Holmden; Frantisek Veselovsky; Vaclav Kachlik; Jakub Hruška; Frantisek Laufek; Tomas Paces; Arnost Komarek; Ondrej Sebek; Marketa Stepanova; et al. (Environmental Science and Pollution Research, 2024)
Nutrient imbalances may negatively affect the health status of forests exposed to multiple stress factors, including drought and bark beetle calamities. We studied the origin of base cations in runoff from a small Carpathian catchment underlain by base-poor flysch turbidites using magnesium (Mg), calcium (Ca) and strontium (Sr) isotope composition of 10 ecosystem compartments. Our objective was to constrain conclusions drawn from long-term hydrochemical monitoring of inputs and outputs. Annual export of Mg, Ca and Sr exceeds 5-to-15 times their atmospheric input. Mass budgets per se thus indicate sizeable net leaching of Mg, Ca and Sr from bedrock sandstones and claystones. Surprisingly, δ 26 Mg, δ 44 Ca and 87 Sr/ 86 Sr isotope ratios of runoff were practically identical to those of atmospheric deposition and soil water but significantly different from bedrock isotope ratios. We did not find any carbonates in the studied area as a hypothetical, easily dissolvable source of base cations whose isotope composition might corroborate the predominance of geogenic base cations in the runoff. Marine carbonates typically have lower δ 26 Mg and 87 Sr/ 86 Sr ratios, and silicate sediments often have higher δ 26 Mg and 87 Sr/ 86 Sr ratios than runoff at the study site. Mixing of these two sources, if confirmed, could reconcile the flux and isotope data.

Products and yields for the NO3 radical initiated atmospheric degradation of 2-methylfuran (2-MF, CH3–C4H3O) - Fatima Al Ali; Cécile Cœur; Nicolas Houzel; Paul Genevray; Fabrice Cazier; Arnaud Cuisset; Vassileios C. Papadimitriou; Alexandre Tomas; Manolis N. Romanias (Atmospheric Environment, 2024)

Trace metal biomonitoring in the farming of tambaqui (Colossoma macropomum), an Amazonian neotropical fish - Edson Luniere Porto; Matheus Gomes da Cruz; Marcos Alexandre Bolson; Ézio Sargetini Junior; Maurício Laterça Martins; Gabriela Tomas Jerônimo (Environmental Science and Pollution Research, 2024)

Soil δ15N spatial distribution is primarily shaped by climatic patterns in the semiarid Caatinga, Northeast Brazil - Alexandre T. Brunello; Gabriela B. Nardoto; Fábio Luís S. Santos; João Paulo Sena-Souza; Carlos A.N. Quesada; Jonathan J. Lloyd; Tomas F. Domingues (Science of The Total Environment, 2024)

The end of an entire biome? World's largest wetland, the Pantanal, is menaced by the Hidrovia project which is uncertain to sustainably support large-scale navigation - Karl M. Wantzen; Mario Luis Assine; Ieda Maria Bortolotto; Debora Fernandes Calheiros; Zilca Campos; Agostinho Carlos Catella; Rafael Morais Chiaravalotti; Walter Collischonn; Eduardo Guimarães Couto; Catia Nunes da Cunha; Geraldo Alves Damasceno-Junior; Carolina Joana da Silva; et al. (Science of The Total Environment, 2024)

Geographic Drivers of Genetic and Plumage Color Diversity in the Blue-Crowned Manakin - Pedro Paulo; Fernando Henrique Teófilo; Carolina Bertuol; Érico Polo; Andre E. Moncrieff; Lucas N. Bandeira; Claudia Nuñez-Penichet; Igor Yuri Fernandes; Mariane Bosholn; Arielli F. Machado; Leilton Willians Luna; Willian Thomaz Peçanha; et al. (Evolutionary Biology, 2023)

Addressing chemical pollution in biodiversity research - Gabriel Sigmund; Marlene Ågerstrand; Alexandre Antonelli; Thomas Backhaus; Tomas Brodin; Miriam L. Diamond; Walter R. Erdelen; David C. Evers; Thilo Hofmann; Thorsten Hueffer; Adelene Lai; Joao P. M. Torres; et al. (Global Change Biology, 2023)
Climate change, biodiversity loss, and chemical pollution are planetary‐scale emergencies requiring urgent mitigation actions. As these “triple crises” are deeply interlinked, they need to be tackled in an integrative manner. However, while climate change and biodiversity are often studied together, chemical pollution as a global change factor contributing to worldwide biodiversity loss has received much less attention in biodiversity research so far. Here, we review evidence showing that the multifaceted effects of anthropogenic chemicals in the environment are posing a growing threat to biodiversity and ecosystems. Therefore, failure to account for pollution effects may significantly undermine the success of biodiversity protection efforts. We argue that progress in understanding and counteracting the negative impact of chemical pollution on biodiversity requires collective efforts of scientists from different disciplines, including but not limited to ecology, ecotoxicology, and environmental chemistry. Importantly, recent developments in these fields have now enabled comprehensive studies that could efficiently address the manifold interactions between chemicals and ecosystems. Based on their experience with intricate studies of biodiversity, ecologists are well equipped to embrace the additional challenge of chemical complexity through interdisciplinary collaborations. This offers a unique opportunity to jointly advance a seminal frontier in pollution ecology and facilitate the development of innovative solutions for environmental protection.

Water content as a deterministic factor in the assessment of cohesive character in soils of Coastal Tablelands (Northeast, Brazil) - Alexandre dos Santos Queiroz; Carlos Tadeu dos Santos Dias; Angélica da Silva Lopes; Ícaro Vasconcelos do Nascimento; Lucas de Sousa Oliveira; Brivaldo Gomes de Almeida; José Coelho de Araújo Filho; Luciano da Silva Souza; Marlen Barros e Silva; Ricardo Espíndola Romero; Raul Shiso Toma; Helon Hébano de Freitas Sousa; et al. (Geoderma Regional, 2023)

Diversification of the Pristimantis conspicillatus group (Anura: Craugastoridae) within distinct neotropical areas throughout the Neogene - Antoine Fouquet; Alexandre Réjaud; Miguel T. Rodrigues; Santiago R. Ron; Juan C. Chaparro; Mariela Osorno; Fernanda P. Werneck; Tomas Hrbek; Albertina P. Lima; Teresa Camacho-Badani; Andres F. Jaramillo-Martinez; Jérôme Chave (Systematics and Biodiversity, 2022)

Bioaccumulation of trace metals in Neoechinorhynchus buttnerae and in its fish host tambaqui (Colossoma macropomum) from fish farms - Gabriela Tomas Jerônimo; Edson Luniere Porto; Marcos Alexandre Bolson; Ézio Sargentini-Júnior; Maurício Laterça Martins; Matheus Gomes da Cruz (Environmental Science and Pollution Research, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia - Antoine Fouquet; Pedro Marinho; Alexandre Réjaud; Thiago R. Carvalho; Marcel A. Caminer; Martin Jansen; Raíssa N. Rainha; Miguel T. Rodrigues; Fernanda P. Werneck; Albertina P. Lima; Tomas Hrbek; Ariovaldo A. Giaretta; et al. (Systematics and Biodiversity, 2021)

Historical biogeography identifies a possible role of Miocene wetlands in the diversification of the Amazonian rocket frogs (Aromobatidae: Allobates ) - Alexandre Réjaud; Miguel T. Rodrigues; Andrew J. Crawford; Santiago Castroviejo‐Fisher; Andrés F. Jaramillo; Juan C. Chaparro; Frank Glaw; Giussepe Gagliardi‐Urrutia; Jiří Moravec; Ignacio J. De la Riva; Pedro Perez; Albertina P. Lima; et al. (Journal of Biogeography, 2020)
Aim We investigate the spatiotemporal context of the diversification of Allobates , a widespread genus of Amazonian frogs with high species diversity particularly in western Amazonia. We tested if that diversity originated in situ or through repeated dispersals from other Amazonian areas and if this diversification took place during or after the Pebas system, a vast lacustrine system occupying most western Amazonia between 23 and 10 million years ago (Mya). Location Amazonia. Taxon Allobates (Anura: Aromobatidae). Methods We gathered a spatially and taxonomically extensive sampling of mitochondrial DNA sequences from 932 Allobates specimens to delimit Operational Taxonomic Units (OTUs). Complete mitogenomes of these OTUs were assembled to reconstruct a time‐calibrated phylogeny used to infer the historical and spatial origin of the Amazonian Allobates lineages. Results Phylogenetic analyses and ancestral area reconstruction suggested that most of the western Amazonian lineages resulted from in situ diversification and that these events occurred between the inferred origin of the genus (25 Mya) and 10 Mya, with a possible peak between 14 and 10 Mya. Dispersal among areas mostly occurred from western Amazonia towards the Brazilian and the Guiana Shields. Closely related Allobates OTUs display an allopatric pattern of distribution, matching interfluves delimited by modern Amazonian rivers. Main Conclusions In western Amazonia, diversification of Allobates appears to have been simultaneous with the last stages of the Pebas system (14–10 Mya). Subsequently (within the last 10 Mya), modern Amazonian river courses shaped the distribution pattern of Allobates species and possibly promoted allopatric speciation.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Reaction of OH Radicals with Acetone: Determination of the Branching Ratio for the Abstraction Pathway at 298 K and 1 Torr - Estelle Turpin; Christa Fittschen; Alexandre Tomas; Pascal Devolder (Journal of Atmospheric Chemistry, 2003)